The role of transparency in combating administrative corruption and promoting the rights of Iraqi citizens - Mohsen Qadir / mohammed nooruldin majid ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The phenomenon of administrative corruption is considered an ancient phenomenon in human history and at the same time a new one, as it has deep roots in most societies, if not all of them. The manifestations of administrative corruption differ from one society to another, and it represents a challenge to all categories of basic human rights, and with the acceleration of technological progress. The development of information technologies and the secret transfer of funds in the absence of basic freedoms, lack of transparency, media, and concepts of accounting and accountability, which facilitated the spread of the phenomenon of corruption and strengthened it. Therefore, countries must keep pace with developments and ensure the activation of the concepts of transparency in their administrative systems, in a way that enhances transparency and strengthens the fight against corruption, which contributes to In promoting administrative development and achieving economic and social progress.